Closing county-level yield gaps through better phosphorus fertilizer management in Northeast China - Shi, Wuliang; Zhang, Yubin; Peng, Mengsu; Shi, Yang; Li, Wei; Liu, Pan; Li, Zheng; Song, Lixin; Cao, Ning; Cui, Jinhu; Cui, Zhenling (Frontiers in Environmental Science, 2022)
The limited available information on variations in yield gaps (differences between actual yields and the theoretically attainable yields) restricts the development of rational strategies to optimize yields and reduce environmental costs. Quantifying the yield potential and the variations in yield gaps will help identify factors that limit yields and will enable a narrowing of the current yield gap. Here, we applied an analytical framework to yield data to identify options for closing the yield gap at the county level. We used a database containing yields for 40 counties and data from 87 representative on-farm experiments in Jilin Province, China, from 2006 to 2008. The yield potential was simulated for each region-year using a Hybrid-Maize model (http://www.hybridmaize.unl.edu/) and weather data. We then conducted a systematic and spatial analysis of actual yields to identify yield gaps at the county level. The simulated average potential yield at 27 representative sites was 15.2 Mg ha−1 (range 8.1–17.6 Mg ha−1) in Jilin Province. The on-farm experiments suggested an attainable potential yield ranging from 8.7 to 16.7 Mg ha−1 across Jilin Province. During this period, the actual maize yield varied between 4.1 and 11.9 Mg ha−1, according to the county-level data. Farmers’ fields, therefore, achieved 52% of the model yield potential and 77% of the attainable potential yield. Widely different amounts of P fertilizer input among farmers contributed significantly to regional variations in YGE. Soil Olsen-P and rainfall were also major factors. The results indicate that there is great potential to substantially increase the maize yield in non-optimal P management regions, such as in the western Jilin Province. Hence, improvements in regional P management strategies, such as at the county level, need to be assessed separately to provide a basis for increasing the actual maize yield.